2,4-Di-tert-butylphenol (2,4-DTBP) purified from streptomyces sp. KCA1 from phyllanthus niruri: isolation, characterization, antibacterial and anticancer properties - Seenivasan, Ayswarya; Manikkam, Radhakrishnan; Kaari, Manigundan; Sahu, Amit Kumar; Said, Madhukar; Dastager, Syed G. (Journal of King Saud University Science, 2022)
Objectives: The present study reports the bioactivity of 2,4-Di-tert-butylphenol (2,4-DTBP) purified from an endophytic Streptomyces species KCA1 isolated from the leaves of Phyllanthus niruri and its antibacterial and anticancer properties. Methods: The extracellular metabolites were produced from the strain KCA1 by submerged fermentation using ethyl acetate. The crude extract was further evaluated for antibacterial activity against set of pathogens. Active metabolite from the extract was purified using chromatography techniques and detected its antibacterial activity by disc diffusion assay. The molecular structure of the active molecule was identified through various spectral study. Moreover, the bioactive metabolite 2,4-DTBP was analyzed antibacterial and anti-proliferative activity. Results: Strain KCA1 was identified as Streptomyces sp. In the preliminary screening, the crude extract exhibited broad spectrum activity against various bacterial pathogens. Based on the spectral properties, the active metabolite was identified as 2,4-Di-tert-butylphenol. The MIC of active compound 2,4-DTBP inhibited E. coli ATCC 25922 and S. aureus ATCC 29213 at 50 lg/ml and 0.78 lg/ml, respectively. The IC50 value of 2,4-DTBP was found to be 11.0 lg/ml and 116.8 lg/ml, against breast cancer cell line (MCF7) and normal VERO cell line, respectively. Conclusions: This study concluded that 2,4-DTBP, produced from the endophytic Streptomyces sp. KCA1, is the potential candidate to develop as promising antibacterial and anticancer agent. (C) 2022 The Authors. Published by Elsevier B.V. on behalf of King Saud University.
Keywords: 2; 4-Di-tert-butylphenol; Antibacterial; antiproliferative activity; Endophytic Streptomyces